The Subsistence Strategy of Linear Pottery Culture in Moravia (Czech Republic): Current State of Knowledge - Čerevková Alžběta (De Gruyter, 2021)
The main goal of this article is to present an overview of current knowledge about the subsistence strategy of Linear Pottery culture (LBK) in Moravia, Czech Republic. The main aspect of the subsistence strategy mentioned here will be the issue of dietary. Early Neolithic sites that in some way contributed to the knowledge about the dietary character (both meat and plant food) will be presented here. On this occasion, a case study of the Žádovice site, which belongs to the most recently analyzed settlements, will be presented. In addition, the methods used in the subsistence strategy of LBK in Moravia will be mentioned. The existing knowledge will be included in a broader settlement context and will be compared with each other. For the time being, it seems that in terms of the species spectrum of farmed animals, the area of Moravia does not differ from the situation known from Central Europe. Certain geographical differences are possible in Moravia, but this hypothesis must be verified in the future, depending on the expansion of the database. The study thus represents a springboard for further research in this area.